2017
DOI: 10.1159/000481171
|View full text |Cite
|
Sign up to set email alerts
|

Early Environmental Enrichment Enhances Abnormal Brain Connectivity in a Rabbit Model of Intrauterine Growth Restriction

Abstract: Introduction: The structural correspondence of neurodevelopmental impairments related to intrauterine growth restriction (IUGR) that persists later in life remains elusive. Moreover, early postnatal stimulation strategies have been proposed to mitigate these effects. Long-term brain connectivity abnormalities in an IUGR rabbit model and the effects of early postnatal environmental enrichment (EE) were explored. Materials and Methods: IUGR was surgically induced in one horn, whereas the contralateral one produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…Analysis of the neonatal rat brain using a combination of advanced MRI analysis and histology demonstrates that gray and white matter microstructure is normalized with lactoferrin supplementation, myelination is protected and measures of axonal integrity and brain organization are restored in rats with lactoferrin supplementation (201). Early environment enrichment or postnatal stimulation has also been shown to have some benefits in brain connectivity in a rabbit model of FGR (203). While there are no current published studies on stem cell therapy for FGR related brain injury, our lab and others are working on testing their applications in FGR and other pregnancy complications (204).…”
Section: Specific Neonatal Morbidities (Table 1)mentioning
confidence: 99%
“…Analysis of the neonatal rat brain using a combination of advanced MRI analysis and histology demonstrates that gray and white matter microstructure is normalized with lactoferrin supplementation, myelination is protected and measures of axonal integrity and brain organization are restored in rats with lactoferrin supplementation (201). Early environment enrichment or postnatal stimulation has also been shown to have some benefits in brain connectivity in a rabbit model of FGR (203). While there are no current published studies on stem cell therapy for FGR related brain injury, our lab and others are working on testing their applications in FGR and other pregnancy complications (204).…”
Section: Specific Neonatal Morbidities (Table 1)mentioning
confidence: 99%
“…A study in FGR (small for gestational age infants) and AGA neonates showed lower FA and higher diffusivity (AD, MD, RD) in FGR infants as compared to AGA infants in a number of brain regions out of a total of 122 brain regions studied (Wang et al, 2017). Similarly, a study in FGR rabbits also showed altered brain networks and decreased FA in the hippocampus (Illa et al, 2018). We did not observe any changes in DTI measures in the six brain regions studied within the FGR lamb brain.…”
Section: Discussionmentioning
confidence: 90%
“…An analysis performed for a subgroup of fetuses that weighed less than 30 grams (which correspond to the 10 th centile of normally distributed weight at birth [ 3 , 6 , 34 36 ]) revealed that a significantly higher proportion of IUGR-T animals with that weight were alive compared to IUGR animals ( Fig 2B ).…”
Section: Resultsmentioning
confidence: 99%